Titanium dioxide supported ruthenium catalyst for selective hydrogenolysis of polyolefins based on support size effect, and preparation method and application thereof
Patent Information
- Application Number
- CN202611085733.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的在于解决现有聚烯烃氢解催化剂缺乏对载体尺寸效应的有效调控引起的催化活性受限且难以高选择性生成液态烷烃产物的技术问题
[0024]本发明通过载体尺寸调控,改善了二氧化钛负载钌催化剂的催化活性。在较中等尺寸的二氧化钛负载钌催化剂中,钌纳米颗粒尺寸较大,载体比表面积更大,且缺陷度更高。钌纳米颗粒与二氧化钛之间的金属-载体相互作用更显著,有效的改善了钌位点的电荷状态和底物吸附能力,提升氢溢流效应,使聚烯烃氢解反应中能在一定条件下高选择性的生成液态烷烃产物。该催化剂在聚烯烃氢解反应中表现出优异的稳定性,反应结束后催化剂可以回收再利用,并且能够适用于低密度聚乙烯和高密度聚乙烯中至少一种聚烯烃塑料的氢解,可以拓展到商用废弃塑料的氢解制燃料油。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of supported ruthenium catalyst technology, specifically relating to a titanium dioxide supported ruthenium catalyst for selective hydrogenolysis of polyolefins based on support size effect, its preparation method and application. Background Technology
[0002] Polyolefins are the world's most produced plastics. Chemical upgrading and recycling of polyolefins via hydrogenolysis can convert plastic resources into natural gas and liquid fuels (Nat. Commun. 2023, 14, 4242). Furthermore, the unique nature of the depolymerization process effectively suppresses undesirable coking, resulting in catalyst stability and controllable product yield.
[0003] In the field of polyolefin hydrogenolysis, researchers have long focused on the regulation of metal centers, that is, by optimizing the types of metals, such as Ru (Appl. Catal. B: Environ. Energy 2022, 318, 121870), Pt (J. Am. Chem. Soc. 2023, 145, 17936-17944), Co (J. Am. Chem. Soc. 2024, 146, 10655-10665.), and Ni (Appl. Catal. B: Environ. Energy 2025, 373, 125359), and designing alloys or single-atom sites to improve performance. In fact, in addition to the regulation of catalytic activity by metal centers, the size of the support is also an important regulatory dimension. As the support and synergist of the active center, changes in its size directly alter the strength of the metal-support interaction, the interfacial electronic structure, and the reaction mass transfer process. Although Rosseinsky's team has modulated the catalytic activity of hydrogenolysis of polyolefins by changing the crystal form of the support (J. Mater. Chem. A 2025, 13, 2032-2046), the mechanism by which the support size affects the hydrogenolysis of polyolefins has not yet been solved.
[0004] In recent years, the influence of support size on catalytic activity has attracted widespread attention from researchers in various fields. For example, Hensen et al. found that the size of the cerium dioxide support determines the reactivity of atomically dispersed palladium catalysts in carbon monoxide, with smaller-sized cerium dioxide catalysts exhibiting exceptionally high activity (Science 2023, 380, 1174-1178). Tang's research group proposed that the valence state of iridium species on the catalyst surface and the performance differences of CO-SCR catalysts vary among catalysts with different support sizes, and that Ir-based catalysts exhibit better nitric oxide catalytic activity on supports with medium particle sizes (Appl. Catal. B: Environ. Energy 2026, 383, 126063). This support effect can be manifested in the fact that support size can determine the distribution of active sites, the mass transfer pathway between reactants and products, and the spatial matching between the support and reactants and products, thereby effectively improving catalytic activity. Therefore, in order to improve the influence mechanism of support size on the hydrogenolysis mechanism of polyolefins, it is necessary to develop a catalyst with controllable support size to efficiently hydrogenolyze polyolefins into high-value products. Summary of the Invention
[0005] The purpose of this invention is to solve the technical problem that existing polyolefin hydrogenolysis catalysts lack effective control over the support size effect, resulting in limited catalytic activity and difficulty in generating liquid alkane products with high selectivity.
[0006] To achieve the above objectives, the present invention employs the following technical means:
[0007] This invention provides a titanium dioxide-supported ruthenium catalyst for selective hydrogenolysis of polyolefins based on support size effect, comprising anatase titanium dioxide support and ruthenium nanoparticles supported on the surface of the support; the particle size of the anatase titanium dioxide support is 5 nm to 100 nm, and the loading of the ruthenium nanoparticles is 1 wt.% to 3 wt.% based on the total weight of the titanium dioxide-supported ruthenium catalyst.
[0008] In the above scheme, the particle size of the anatase titanium dioxide support is preferably 20-30 nm, and more preferably 25 nm.
[0009] This invention also provides a method for preparing a titanium dioxide-supported ruthenium catalyst, comprising the following steps:
[0010] Step (1) Anatase titanium dioxide with a particle size of 5 nm to 100 nm is subjected to a first calcination treatment to obtain pretreated titanium dioxide;
[0011] Step (2) The pretreated titanium dioxide is dispersed in a solvent, ruthenium salt solution is added and mixed, and then a reducing agent solution is added to carry out a reduction reaction. The solid precursor is obtained by solid-liquid separation.
[0012] Step (3) The solid precursor is subjected to a second calcination treatment under a reducing atmosphere to obtain the titanium dioxide supported ruthenium catalyst.
[0013] In the above scheme, in step (1), the temperature of the first calcination treatment is 300 ℃ ~ 450 ℃, and the time is 4h ~ 8h;
[0014] In step (3), the temperature of the second calcination treatment is 300 ℃ ~ 500 ℃, and the time is 2 h ~ 6 h; the reducing atmosphere is a mixed atmosphere of hydrogen and inert gas, wherein the volume fraction of hydrogen is 1% ~ 10%.
[0015] In the above scheme, in step (2), the ruthenium salt is ruthenium chloride, and the reducing agent is sodium borohydride;
[0016] The mass ratio of ruthenium in the ruthenium chloride to the anatase titanium dioxide is 0.01 ~ 0.03:1; the molar ratio of ruthenium chloride to sodium borohydride is 1: (5 ~ 10).
[0017] In the above scheme, in step (2), the molar concentration of the ruthenium salt solution is 1.2 mmol / L ~ 3.6 mmol / L, and the molar concentration of the reducing agent solution is 12 mmol / L ~ 60 mmol / L; the solvent includes at least one of water, methanol or ethanol.
[0018] The present invention also provides an application of a titanium dioxide-supported ruthenium catalyst in the hydrogenolysis reaction of polyolefins, wherein the titanium dioxide-supported ruthenium catalyst is the titanium dioxide-supported ruthenium catalyst as described in claim 1 or 2.
[0019] In the above scheme, the conditions for the hydrogenolysis reaction of the polyolefin include: a reaction temperature of 220 ℃ ~ 260 ℃, a hydrogen pressure of 1 MPa ~ 3 MPa, and a reaction time of 2 h ~ 10 h;
[0020] The mass ratio of the polyolefin to the titanium dioxide-supported ruthenium catalyst is 1:(0.05~0.15).
[0021] In the above scheme, the polyolefin includes at least one of low-density polyethylene, high-density polyethylene, linear low-density polyethylene and polypropylene; preferably, the polyolefin is waste commercial polyolefin plastic.
[0022] In the above scheme, after the polyolefin hydrogenolysis reaction is completed, the process further includes separating, washing and drying the titanium dioxide-supported ruthenium catalyst, and recycling it for the next polyolefin hydrogenolysis reaction.
[0023] Because the present invention employs the above-mentioned technical means, it has the following beneficial effects:
[0024] This invention improves the catalytic activity of titanium dioxide-supported ruthenium catalysts by controlling the size of the support. In medium-sized titanium dioxide-supported ruthenium catalysts, the ruthenium nanoparticles are larger, the support has a larger specific surface area, and the defect degree is higher. The metal-support interaction between the ruthenium nanoparticles and titanium dioxide is more significant, effectively improving the charge state of the ruthenium sites and the substrate adsorption capacity, enhancing the hydrogen spillover effect, and enabling the high-selectivity generation of liquid alkane products in the hydrogenolysis reaction of polyolefins under certain conditions. This catalyst exhibits excellent stability in the hydrogenolysis reaction of polyolefins, can be recycled and reused after the reaction, and is applicable to the hydrogenolysis of at least one polyolefin plastic in low-density polyethylene and high-density polyethylene, and can be extended to the hydrogenolysis of commercial waste plastics to produce fuel oil.
[0025] In this invention, by controlling the size of the titanium dioxide support, the distribution and valence state of the ruthenium metal centers can be regulated, and the metal-support interaction between the ruthenium metal centers and titanium dioxide can be improved. Therefore, adjusting the support size can greatly improve the interaction between the metal centers and the support, enhance the adsorption capacity of the substrate and the hydrogen spillover effect, and thus affect the reactivity.
[0026] The improved Ru / TiO2-25 catalyst of this invention has a larger specific surface area and a higher degree of oxygen vacancy defects, which is conducive to the formation of ruthenium nanoparticles with better dispersion and stronger electronegativity. This results in better mass transfer of reactants in the catalyst channels, while also exhibiting high surface hydrogen coverage and weak alkane adsorption capacity. Therefore, at a weight material ratio of 20:1 (polyolefin:catalyst), this catalyst can achieve a high efficiency of 260 °C. o At C, after 4 h of reaction, polyolefins are completely converted, with a liquid alkane yield of 92%. Ru / TiO2-25 can be used for the hydrogenolysis of at least one polyolefin plastic in low-density polyethylene and high-density polyethylene, as well as commercial polyolefin plastics, and exhibits good stability and recyclability, with no significant decrease in activity after 8 runs. Therefore, this invention reveals for the first time the regulatory role of the carrier size effect on the hydrogenolysis activity of polyolefins, providing an effective pathway for polyolefin hydrogenolysis. Attached Figure Description
[0027] Figure 1 The XRD pattern of the titanium dioxide-supported ruthenium catalyst prepared in Example 1 of this invention;
[0028] Figure 2 This is a TEM image of the titanium dioxide-supported ruthenium catalyst prepared in Example 1 of this invention;
[0029] Figure 3 The XRD pattern of the titanium dioxide-supported ruthenium catalyst prepared in Example 2 of this invention;
[0030] Figure 4 This is a TEM image of the titanium dioxide-supported ruthenium catalyst prepared in Example 2 of this invention;
[0031] Figure 5 The XRD pattern of the titanium dioxide-supported ruthenium catalyst prepared in Example 3 of this invention;
[0032] Figure 6 This is a TEM image of the titanium dioxide-supported ruthenium catalyst prepared in Example 3 of the present invention;
[0033] Figure 7 The XRD pattern of the titanium dioxide-supported ruthenium catalyst prepared in Example 4 of this invention;
[0034] Figure 8 This is a TEM image of the titanium dioxide-supported ruthenium catalyst prepared in Example 4 of this invention;
[0035] Figure 9 This is a gas phase diagram showing the product distribution of LDPE hydrogenolysis using the catalyst Ru / TiO2-25 in Example 5 of this invention.
[0036] Figure 10 This is a gas phase diagram showing the product distribution of LDPE hydrogenated by the catalyst Ru / TiO2-5 in Comparative Example 1 of this invention.
[0037] Figure 11 This is a gas phase diagram showing the product distribution of LDPE hydrogenated using the catalyst Ru / TiO2-60 in Comparative Example 2 of this invention.
[0038] Figure 12 This is a gas phase diagram showing the product distribution of LDPE hydrogenated by the catalyst Ru / TiO2-100 in Comparative Example 3 of this invention. Detailed Implementation
[0039] The embodiments of the present invention will be described in detail below. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, any modifications or equivalent substitutions made to the present invention should be covered within the scope of the claims of the present invention.
[0040] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art will understand that the present invention can be practiced without these specific details.
[0041] Example 1
[0042] This embodiment provides a method for preparing a titanium dioxide-supported ruthenium catalyst, which includes the following steps:
[0043] Step 1: Place 2.4 g of 25 nm anatase titanium dioxide in a tube furnace and heat it at 450 °C in an air atmosphere. o Calcination at C for 6 h yielded the first precursor;
[0044] Step 2: Disperse 300 mg of the first precursor in 60 mL of deionized water to obtain the first mixture;
[0045] Step 3: Dissolve ruthenium chloride in deionized water to obtain a second mixture with a molar concentration of 1.2 mmol / L.
[0046] Step 4: Dissolve sodium borohydride in deionized water to obtain a third mixture with a molar concentration of 12 mmol / L;
[0047] Step 5: Add 25 mL of the second mixture described in Step 3 dropwise to the first mixture obtained in Step 2, and stir at room temperature to obtain the fourth mixture;
[0048] Step Six: Add 25 mL of the third mixture described in Step Four to the fourth mixture described in Step Five, and stir at room temperature to obtain the fifth mixture;
[0049] Step 7: The fifth mixture described in Step 6 is centrifuged, washed, and dried to obtain the second precursor;
[0050] Step 8: The second precursor described in Step 7 is subjected to an Ar / H2 (5 vol%) atmosphere at 450 °C. o The titanium dioxide-supported ruthenium catalyst (Ru / TiO2-25) was obtained by C reduction for 4 h.
[0051] The XRD and TEM images of its titanium dioxide-supported ruthenium catalyst are as follows: Figure 1 and Figure 2 As shown, where:
[0052] Figure 1 The XRD pattern of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-25) shows that titanium dioxide is a single anatase phase and there are no diffraction peaks of Ru species, indicating that Ru species have high dispersibility.
[0053] Figure 2 TEM images of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-25) show that the titanium dioxide is approximately 25 nm in size and contains small ruthenium nanoparticles.
[0054] Example 2
[0055] This embodiment provides a method for preparing a titanium dioxide-supported ruthenium catalyst, which includes the following steps:
[0056] Step 1: Place 2.4g of 5nm anatase titanium dioxide in a tube furnace and heat it at 450°C in an air atmosphere. o Calcination with C for 6 hours yielded the first precursor;
[0057] Step 2: Disperse 300 mg of the first precursor in 60 mL of deionized water to obtain the first mixture;
[0058] Step 3: Dissolve ruthenium chloride in deionized water to obtain a second mixture with a molar concentration of 1.2 mmol / L.
[0059] Step 4: Dissolve sodium borohydride in deionized water to obtain a third mixture with a molar concentration of 12 mmol / L;
[0060] Step 5: Add 25 mL of the second mixture described in Step 3 dropwise to the first mixture obtained in Step 2, and stir at room temperature to obtain the fourth mixture;
[0061] Step Six: Add 25 mL of the third mixture described in Step Four to the fourth mixture described in Step Five, and stir at room temperature to obtain the fifth mixture;
[0062] Step 7: The fifth mixture described in Step 6 is centrifuged, washed, and dried to obtain the second precursor;
[0063] Step 8: The second precursor described in Step 7 is subjected to an Ar / H2 (5 vol%) atmosphere at 450 °C. o The titanium dioxide-supported ruthenium catalyst (Ru / TiO2-5) was obtained by C reduction for 4 h.
[0064] The XRD and TEM images of its titanium dioxide-supported ruthenium catalyst are as follows: Figure 3 and Figure 4 As shown, where:
[0065] Figure 3 The XRD pattern of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-5) shows that titanium dioxide is a single anatase phase and there are no diffraction peaks of Ru species, indicating that Ru species have high dispersibility.
[0066] Figure 4 TEM images of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-5) show that the titanium dioxide has a size of about 5~10 nm and contains small ruthenium nanoparticles.
[0067] Example 3
[0068] This embodiment provides a method for preparing a titanium dioxide-supported ruthenium catalyst, which includes the following steps:
[0069] Step 1: Place 2.4 g of 60 nm anatase titanium dioxide in a tube furnace and heat it at 450 °C in an air atmosphere. o Calcination at C for 6 h yielded the first precursor;
[0070] Step 2: Disperse 300 mg of the first precursor in 60 mL of deionized water to obtain the first mixture;
[0071] Step 3: Dissolve ruthenium chloride in deionized water to obtain a second mixture with a molar concentration of 1.2 mmol / L.
[0072] Step 4: Dissolve sodium borohydride in deionized water to obtain a third mixture with a molar concentration of 12 mmol / L;
[0073] Step 5: Add 25 mL of the second mixture described in Step 3 dropwise to the first mixture obtained in Step 2, and stir at room temperature to obtain the fourth mixture;
[0074] Step Six: Add 25 mL of the third mixture described in Step Four to the fourth mixture described in Step Five, and stir at room temperature to obtain the fifth mixture;
[0075] Step 7: The fifth mixture described in Step 6 is centrifuged, washed, and dried to obtain the second precursor;
[0076] Step 8: The second precursor described in Step 7 is subjected to an Ar / H2 (5 vol%) atmosphere at 450 °C. o The titanium dioxide-supported ruthenium catalyst (Ru / TiO2-60) was obtained by C reduction for 4 h.
[0077] The XRD and TEM images of its titanium dioxide-supported ruthenium catalyst are as follows: Figure 5 and Figure 6 As shown, where:
[0078] Figure 5 The XRD pattern of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-60) shows that titanium dioxide is a single anatase phase and there are no diffraction peaks of Ru species, indicating that Ru species have high dispersibility.
[0079] Figure 6TEM images of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-60) show that the titanium dioxide has a size of approximately 60 nm and contains ruthenium nanoparticles with relatively large particle sizes.
[0080] Example 4
[0081] This embodiment provides a method for preparing a titanium dioxide-supported ruthenium catalyst, which includes the following steps:
[0082] Step 1: Place 2.4 g of 100 nm anatase titanium dioxide in a tube furnace and heat it at 450 °C in an air atmosphere. o Calcination at C for 6 h yielded the first precursor;
[0083] Step 2: Disperse 300 mg of the first precursor in 60 mL of deionized water to obtain the first mixture;
[0084] Step 3: Dissolve ruthenium chloride in deionized water to obtain a second mixture with a molar concentration of 1.2 mmol / L.
[0085] Step 4: Dissolve sodium borohydride in deionized water to obtain a third mixture with a molar concentration of 12 mmol / L;
[0086] Step 5: Add 25 mL of the second mixture described in Step 3 dropwise to the first mixture obtained in Step 2, and stir at room temperature to obtain the fourth mixture;
[0087] Step Six: Add 25 mL of the third mixture described in Step Four to the fourth mixture described in Step Five, and stir at room temperature to obtain the fifth mixture;
[0088] Step 7: The fifth mixture described in Step 6 is centrifuged, washed, and dried to obtain the second precursor;
[0089] Step 8: The second precursor described in Step 7 is subjected to an Ar / H2 (5 vol%) atmosphere at 450 °C. o The titanium dioxide-supported ruthenium catalyst (Ru / TiO2-100) was obtained by C reduction for 4 h.
[0090] The XRD and TEM images of its titanium dioxide-supported ruthenium catalyst are as follows: Figure 7 and Figure 8 As shown, where:
[0091] Figure 7 The XRD pattern of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-100) indicates that the titanium dioxide is a single anatase phase, with a value of ~44.0. o The diffraction peaks at that location can be attributed to the Ru species.
[0092] Figure 8 TEM images of the titanium dioxide-supported ruthenium catalyst (Ru / TiO2-100) show that the titanium dioxide is approximately 100 nm in size and contains ruthenium nanoparticles with relatively large particle sizes.
[0093] Example 5
[0094] This embodiment provides a hydrogenolysis reaction preparation process for low-density polyethylene, specifically:
[0095] 1 g of low-density polyethylene and 50 mg of Ru / TiO2-25 prepared in Example 1 were placed in a stainless steel high-pressure reactor. After sealing, the reactor was purged three times with H2 and pressurized to 2 MPa with H2. The reactor was then placed in a preheated heating device and heated to 260°C with stirring at 800 rpm. o C, react for 4 h. After the reaction is complete, cool to room temperature and dissolve the liquid product in dichloromethane. Filter to separate the solid and liquid phases. Dry the solid phase and weigh it. Rotary evaporate the liquid product and weigh it. Calculate the conversion rate as 100%, the yield of C1~C5 products as 12%, and the yield of C6~C35 products as 88%.
[0096] GC analysis of C6~C35 component distribution is as follows Figure 9 As shown.
[0097] Comparative Example 1
[0098] The catalyst Ru / TiO2-5 prepared in Example 2 was used in the hydrogenolysis reaction of low-density polyethylene, specifically:
[0099] 1 g of low-density polyethylene and 50 mg of Ru / TiO2-5 were placed in a stainless steel high-pressure reactor. After sealing, the reactor was purged three times with H2 and pressurized to 2 MPa with H2. The reactor was then placed in a preheated heating device and heated to 260°C with stirring at 800 rpm. o C, react for 4 h. After the reaction is complete, cool to room temperature and dissolve the liquid product in dichloromethane. Filter to separate the solid and liquid phases. Dry the solid phase and weigh it. Rotary evaporate the liquid product and weigh it. Calculate the conversion rate as 28%, the yield of C1~C5 products as 7%, and the yield of C6~C35 products as 21%.
[0100] GC analysis of C6~C35 component distribution is as follows Figure 10 As shown.
[0101] Comparative Example 2
[0102] The catalyst Ru / TiO2-60 prepared in Example 3 was used in the hydrogenolysis reaction of low-density polyethylene, specifically:
[0103] 1 g of low-density polyethylene and 50 mg of Ru / TiO2-60 were placed in a stainless steel high-pressure reactor. After sealing, the reactor was purged three times with H2 and pressurized to 2 MPa with H2. The reactor was then placed in a preheated heating device and heated to 260°C with stirring at 800 rpm. o C, react for 4 h. After the reaction is complete, cool to room temperature and dissolve the liquid product in dichloromethane. Filter to separate the solid and liquid phases. Dry the solid phase and weigh it. Rotary evaporate the liquid product and weigh it. Calculate the conversion rate as 69%, the yield of C1~C5 products as 8%, and the yield of C6~C35 products as 61%.
[0104] GC analysis of C6~C35 component distribution is as follows Figure 11 As shown.
[0105] Comparative Example 3
[0106] The catalyst Ru / TiO2-100 prepared in Example 3 was used in the hydrogenolysis reaction of low-density polyethylene, specifically:
[0107] 1 g of low-density polyethylene and 50 mg of Ru / TiO2-100 were placed in a stainless steel high-pressure reactor. After sealing, the reactor was purged three times with H2 and pressurized to 2 MPa with H2. The reactor was then placed in a preheated heating device and heated to 260°C with stirring at 800 rpm. o C, react for 4 h. After the reaction is complete, cool to room temperature and dissolve the liquid product in dichloromethane. Filter to separate the solid and liquid phases. Dry the solid phase and weigh it. Rotary evaporate the liquid product and weigh it. Calculate the conversion rate as 10%, the yield of C1~C5 products as 6%, and the yield of C6~C35 products as 4%.
[0108] GC analysis of C6~C35 component distribution is as follows Figure 12 As shown.
[0109] Examples 6-8
[0110] Examples 6-8 provide the preparation process of polyolefin hydrogenolysis reaction, which differs from Example 5 in that only the reaction time is changed, as shown in Table 1.
[0111] Table 1. Effect of reaction time on catalytic activity in Examples 6-8
[0112]
[0113] Examples 9-11
[0114] Examples 9-11 provide the hydrogenolysis reaction preparation process of commercial polyolefin plastics, which differs from Example 5 in that only the type of polyolefin substrate is changed, as shown in Table 2.
[0115] Table 2. Effects of HDPE and different commercial polyolefin substrates on catalytic activity in Examples 9-11
[0116]
[0117] Example 12
[0118] Example 12 provides an activity test of catalyst reuse during the preparation of polyolefin hydrogenolysis reaction, specifically:
[0119] 1 g of low-density polyethylene and 50 mg of Ru / TiO2-25 were placed in a stainless steel high-pressure reactor. After sealing, the reactor was purged three times with H2 and pressurized to 2 MPa with H2. The reactor was then placed in a preheated heating device and heated to 260°C with stirring at 800 rpm. o C, reaction time 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid product was dissolved in dichloromethane. The solid and liquid phases were separated by filtration. The solid phase was dried and weighed, and the liquid product was rotary evaporated and weighed. The conversion rate and yield were calculated. The component distribution of the liquid product was analyzed by GC. The conversion rates in the first use of the catalyst and in the first 1-7 reuses were as follows: 100%, 100%, 100%, 100%, 98%, 98%, 95%, 95%. The yields of the target C1-C5 alkane products in the first use of the catalyst and in the first 1-7 reuses were 12%, 13%, 12%, 11%, 14%, 12%, 13%, 11%, respectively. The yields of the target C6-C35 alkane products in the first use of the catalyst and in the first 1-7 reuses were 88%, 87%, 88%, 89%, 84%, 86%, 82%, 84%, respectively. The catalyst activity showed no significant decrease.
[0120] The above embodiments have provided a detailed description of the implementation of the present invention. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. The above descriptions are merely preferred embodiments of the present invention and do not limit the scope of the present invention. All equivalent structural changes made based on the content of this specification are included within the scope of the present invention.
Claims
1. A titanium dioxide-supported ruthenium catalyst for selective hydrogenolysis of polyolefins based on support size effect, characterized in that, It includes anatase titanium dioxide support and ruthenium nanoparticles loaded on the surface of the support; the particle size of the anatase titanium dioxide support is 5 nm to 100 nm, and the loading amount of the ruthenium nanoparticles is 1 wt.% to 3 wt.% based on the total weight of the titanium dioxide-supported ruthenium catalyst.
2. The titanium dioxide-supported ruthenium catalyst according to claim 1, characterized in that, The anatase titanium dioxide carrier has a particle size of 25 nm.
3. A method for preparing a titanium dioxide-supported ruthenium catalyst as described in claim 1, characterized in that, Includes the following steps: Step (1) Anatase titanium dioxide with a particle size of 5 nm to 100 nm is subjected to a first calcination treatment to obtain pretreated titanium dioxide; Step (2) The pretreated titanium dioxide is dispersed in a solvent, ruthenium salt solution is added and mixed, and then a reducing agent solution is added to carry out a reduction reaction. The solid precursor is obtained by solid-liquid separation. Step (3) The solid precursor is subjected to a second calcination treatment under a reducing atmosphere to obtain the titanium dioxide supported ruthenium catalyst.
4. The preparation method according to claim 3, characterized in that, In step (1), the temperature of the first calcination treatment is 300 ℃ ~ 450 ℃, and the time is 4 h ~ 8 h; In step (3), the temperature of the second calcination treatment is 300 ℃ ~ 500 ℃, and the time is 2 h ~ 6 h; the reducing atmosphere is a mixed atmosphere of hydrogen and inert gas, wherein the volume fraction of hydrogen is 1% ~ 10%.
5. The preparation method according to claim 3, characterized in that, In step (2), the ruthenium salt is ruthenium chloride, and the reducing agent is sodium borohydride; The mass ratio of ruthenium in the ruthenium chloride to the anatase titanium dioxide is 0.01 ~ 0.03 : 1; the molar ratio of ruthenium chloride to sodium borohydride is 1 : (5 ~ 10).
6. The preparation method according to claim 3, characterized in that, In step (2), the molar concentration of the ruthenium salt solution is 1.2 mmol / L to 3.6 mmol / L, and the molar concentration of the reducing agent solution is 12 mmol / L to 60 mmol / L; the solvent includes at least one of water, methanol or ethanol.
7. The application of a titanium dioxide-supported ruthenium catalyst in the hydrogenolysis reaction of polyolefins, characterized in that, The titanium dioxide-supported ruthenium catalyst is the titanium dioxide-supported ruthenium catalyst according to any one of claims 1 or 2.
8. The application according to claim 7, characterized in that, The conditions for the hydrogenolysis reaction of the polyolefin include: a reaction temperature of 220 ℃ ~ 260 ℃, a hydrogen pressure of 1 MPa ~ 3 MPa, and a reaction time of 2 h ~ 10 h; The mass ratio of the polyolefin to the titanium dioxide-supported ruthenium catalyst is 1:(0.05~0.15).
9. The application according to claim 7, characterized in that, The polyolefin includes at least one of low-density polyethylene and high-density polyethylene; preferably, the polyolefin is waste commercial polyolefin plastic.
10. The application according to claim 7, characterized in that, After the polyolefin hydrogenolysis reaction is completed, the process further includes separating, washing and drying the titanium dioxide-supported ruthenium catalyst, and recycling it for the next polyolefin hydrogenolysis reaction.
